The effect of concomitant cholecystectomy and sleeve gastrectomy on morbidity in high-risk obese patients with symptomatic gallstones - Dincer, Mursit; Dogan, Fadli (Termedia Publishing House Ltd, 2019)
Introduction: Obesity is an independent risk factor for gallstones. In obese patients, gallstone is more symptomatic than in non-obese people. Aim: To present the early results of laparoscopic sleeve gastrectomy (LSG) and concomitant cholecystectomy (CC) performed in patients with symptomatic gallstone accompanied by at least one additional systemic disease to obesity and to investigate its effect on morbidity. Material and methods: Patients undergoing sleeve gastrectomy for morbid obesity between January 2016 and August 2018 were retrospectively studied. Twenty-seven patients who underwent laparoscopic sleeve gastrectomy and concomitant cholecystectomy due to symptomatic gallstone stones were included in this study. The patients were divided into two groups according to the applied surgical technique: laparoscopic sleeve gastrectomy and concomitant cholecystectomy (n = 27) and laparoscopic sleeve gastrectomy (n = 70). The results of an additional operation on these patients and their perioperative complications were evaluated. Results: A total of 97 patients were included in the study. The mean age of the patients was 40.58 +/- 10.36 years. There was no statistically significant difference between groups in terms of complications (p = 0.669). The difference in the duration of the operation was statistically significant (p < 0.001). Conclusions: Concomitant cholecystectomy may be presented as an alternative surgical procedure due to the demonstration that concomitant cholecystectomy can be performed safely in comorbid obese patients, with a risk of becoming symptomatic in the rest of life at a certain rate, and low risk of complications in asymptomatic patients.
Keywords: obesity; sleeve gastrectomy; gallstones; concomitant cholecystectomy; high-risk patient